2019
DOI: 10.1007/s40820-019-0270-4
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight and High-Performance Microwave Absorber Based on 2D WS2–RGO Heterostructures

Abstract: HIGHLIGHTS • WS 2-rGO nanosheets with ultra-small thicknesses and ultra-lightweight, were successfully prepared by a facile hydrothermal method. • The WS 2-rGO isomorphic heterostructures exhibited remarkable microwave absorption properties. ABSTRACT Two-dimensional (2D) nanomaterials are categorized as a new class of microwave absorption (MA) materials owing to their high specific surface area and peculiar electronic properties. In this study, 2D WS 2-reduced graphene oxide (WS 2-rGO) heterostructure nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(86 citation statements)
references
References 61 publications
1
84
0
1
Order By: Relevance
“…Secondly, dielectric loss produced by the polarization of dipoles and interfaces among the Fe, TiO 2 , and carbon would give a great contribution to transform the EM energy into thermal energy. In detail, the Fe, TiO 2 nanoparticles, and carbon sheets with different conductivity could form capacitor-like structure, such as the contact positions of carbon sheets, the interfaces of Fe-TiO 2 , Fe-C, and TiO 2 -C. These capacitor-like structures could give rise to the accumulation and rearrangement of space charge, resulting in generating vast interface polarization processes in alternating EM field [3,75,76]. Thus, the interfacial polarization played a main role in the EM attenuation process for this sandwich-like Fe&TiO 2 @C ternary nanocomposite.…”
Section: Electromagnetic Parameters and Microwave Absorption Performancementioning
confidence: 99%
“…Secondly, dielectric loss produced by the polarization of dipoles and interfaces among the Fe, TiO 2 , and carbon would give a great contribution to transform the EM energy into thermal energy. In detail, the Fe, TiO 2 nanoparticles, and carbon sheets with different conductivity could form capacitor-like structure, such as the contact positions of carbon sheets, the interfaces of Fe-TiO 2 , Fe-C, and TiO 2 -C. These capacitor-like structures could give rise to the accumulation and rearrangement of space charge, resulting in generating vast interface polarization processes in alternating EM field [3,75,76]. Thus, the interfacial polarization played a main role in the EM attenuation process for this sandwich-like Fe&TiO 2 @C ternary nanocomposite.…”
Section: Electromagnetic Parameters and Microwave Absorption Performancementioning
confidence: 99%
“…7d, EM waves can travel long distances with multi-reflected propagation paths inside the hybrids, resulting from the special layered structures of the WS 2 nanosheets [72]. Table 1 compares the EM wave absorption characteristics of some hybrid materials containing 2D materials reported in previous work [16,17,37,39,40]. It is found that the WS 2 /NiO hybrids with heterostructures prepared in this work have excellent EM wave absorption properties, as compared with other EMA materials.…”
Section: Resultsmentioning
confidence: 77%
“…The HRTEM image of the WS 2 / NiO hybrids is shown in Fig. 2e, and the interlayer spacing of approximately 0.62 and 0.24 nm could be indexed to the WS 2 and NiO crystallography planes, respectively [39,57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As science and technology develop dramatically fast, electromagnetic radiation pollution has become a growing problem due to the explosive growth in the application of electronic devices, such as radar systems, local area networks, telephones, and computers. Overexposure to electromagnetic wave can not only affect the functioning of electronic equipment but also be potentially detrimental to human being and raise severe problems concerning the field of military applications [1][2][3]. Therefore, it has spurred internationally unprecedented interest in exploring microwave absorbing materials, which converts electromagnetic wave into energy in other forms [4,5].…”
Section: Introductionmentioning
confidence: 99%